2018
DOI: 10.1029/2018jc014448
|View full text |Cite
|
Sign up to set email alerts
|

Submarine Groundwater Discharge‐Derived Carbon Fluxes in Mangroves: An Important Component of Blue Carbon Budgets?

Abstract: Mangroves are blue carbon systems characterized by high soil carbon storage and sequestration.Soil carbon losses via groundwater or pore water pathways are potentially important yet poorly understood components of mangrove carbon budgets. Here we quantified submarine groundwater discharge (SGD) and associated dissolved inorganic carbon (DIC) and organic carbon (DOC) fluxes into a mangrove-dominated tropical bay (Maowei Sea) using a radon ( 222 Rn) mass balance model. The SGD fluxes in Maowei Sea were estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 94 publications
3
49
1
Order By: Relevance
“…If extrapolated to the global mangrove area, these exchange rates would be enough to filter the entire continental shelf volume in ∼150 years and are equivalent to ∼1/3 of the annual volume of river water entering the oceans (Tait et al, 2016). Because mangrove and saltmarsh porewaters are often highly enriched in carbon and greenhouse gases (Santos et al, 2019), the input of dissolved carbon to the oceans via mangroves may be comparable to the input from global rivers (Chen et al, 2018b). Therefore, muddy mangrove and saltmarsh systems that are widespread on global shorelines deserve additional attention and may disproportionally contribute to SGD and related biogeochemical inputs to the ocean.…”
Section: Geophysical Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…If extrapolated to the global mangrove area, these exchange rates would be enough to filter the entire continental shelf volume in ∼150 years and are equivalent to ∼1/3 of the annual volume of river water entering the oceans (Tait et al, 2016). Because mangrove and saltmarsh porewaters are often highly enriched in carbon and greenhouse gases (Santos et al, 2019), the input of dissolved carbon to the oceans via mangroves may be comparable to the input from global rivers (Chen et al, 2018b). Therefore, muddy mangrove and saltmarsh systems that are widespread on global shorelines deserve additional attention and may disproportionally contribute to SGD and related biogeochemical inputs to the ocean.…”
Section: Geophysical Processesmentioning
confidence: 99%
“…By considering SGD in the DIC budget in the ocean, the sink or source regions of CO 2 have been re-evaluated (Cai et al, 2003;Dorsett et al, 2011;Liu et al, 2012). The importance of SGD-derived DIC fluxes to the oceans have been particularly emphasized in carbon-rich mangrove forest areas (Chen et al, 2018b) and have been suggested to exceed regional river inputs in Florida (Liu et al, 2012) and in an Australian embayment (Stewart et al, 2015). In addition, DIC concentrations in STEs and their associated contributions to the ocean showed large seasonal variations (Wang et al, 2015).…”
Section: Geochemical Processesmentioning
confidence: 99%
“…Because the transport of biogeochemical compounds via advective flushing can be orders of magnitude faster than molecular diffusion (Santos et al ), mass balances overlooking advective pore water transport may underestimate the role played by intertidal wetlands in coastal carbon budgets. A recent global literature summary suggests that pore‐water–derived carbon exports from mangroves can be equivalent to ~ 30% of global river inputs to the oceans (Chen et al ).…”
mentioning
confidence: 99%
“…Assuming uniformly distributed karst aquifers around the globe, which have similar DIC concentration in their groundwater, the global net SGD‐derived DIC flux from karst aquifers would be (0.18–1.06) × 10 13 mol/year. This number equals 8–48% of the DIC flux via SGD in the global mangrove ecosystem that has high DIC export rates and account for 2.7–9.6% of the global riverine DIC inputs (Chen et al, ; Maher et al, ). Just as reported in Chen et al (), if the total SGD‐derived DIC flux is used, then the estimated SGD‐derived DIC flux in global karst aquifers along the coasts equals 17–97% of the flux in the global mangrove ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…This number equals 8–48% of the DIC flux via SGD in the global mangrove ecosystem that has high DIC export rates and account for 2.7–9.6% of the global riverine DIC inputs (Chen et al, ; Maher et al, ). Just as reported in Chen et al (), if the total SGD‐derived DIC flux is used, then the estimated SGD‐derived DIC flux in global karst aquifers along the coasts equals 17–97% of the flux in the global mangrove ecosystem. Therefore, SGD from the DIC‐enriched coastal karst aquifers is likely to be an important but easily ignored source for the carbon budget in the coastal seas worldwide.…”
Section: Discussionmentioning
confidence: 99%